Online Interactive E-Map Learning Tool Using Javascript - Abdullah, Majidin (2008)
The project proposes to set up a prototype online E-Map Learning Tool incorporating terrestrial(earth) map and non-terrestrial(astronomical) map by implementing and leveraging on MAP API JavaScripts.